Orthopedic physical assessment - Magee, D. J. (Saunders Elsevier, 2008)
Newly updated, this full-color resource offers a systematic approach to performing a neuromusculoskeletal assessment with rationales for various aspects of the assessment. This comprehensive text covers every joint of the body, head and face, gait, posture, emergency care, the principles of assessment, and preparticipation evaluation. The latest edition of this core text is the essential cornerstone in the new four-volume musculoskeletal rehabilitation series. Key Features